Developing Aesthetics Assessment Skills in Bachelor of Design Programmes: An Introspective Account in UPSI - Hoe, Tan Wee (Asian Journal of Assessment in Teaching and Learning, 2013)
This paper elaborates how aesthetic assessment skills were developed among undergraduate students who were pursuing Bachelor of Design degree programmes in Sultan Idris Education University. Three assessment methods – criterion-referenced, norm-referenced and ipsative assessment were introduced to the students during their second or third semester of study. The students were guided to develop their aesthetic assessment skills, specifically in the Design Aesthetics Course. One of the intended learning outcomes for the course requires the students to analyse and criticise the aspects contained in art forms which would be learned according to robust verbal and written arguments and evidence. The paper presents how the learning outcome was attained by the students, from learning four principles of aesthetic pleasure and three levels of emotional design, to applying the knowledge in course assignments. They were guided to construct aesthetic criteria and assessment forms, and directed to assess design work for either fictional or real-life clients. The students were also instructed to write an individual assessment report and then present the report to clients through social media. For students who believed they could perform better if they were given a second chance, they could attempt to complete make-good assignments and determine whether they wanted their scores to be replaced or not. Three challenges were encountered by the lecturer in teaching aesthetic assessment skills, i.e. the need to match assignments’ difficulty level with students’ prior learning experience; the need to make the philosophical nature of aesthetics practical for design; and the urge for lifelong learning in order to teach design.